2019
DOI: 10.1002/jor.24219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fatty acid content on humeral cartilage and bone structure in a mouse model of diet‐induced obesity

Abstract: Obesity is a primary risk factor for osteoarthritis (OA), and previous studies have shown that dietary content may play an important role in the pathogenesis of cartilage and bone in knee OA. Several previous studies have shown that the ratio of ω‐3 polyunsaturated fatty acids (PUFAs), ω‐6 PUFAs, and saturated fatty acids can significantly influence bone structure and OA progression. However, the influence of obesity or dietary fatty acid content on shoulder OA is not well understood. The goal of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
(148 reference statements)
0
12
0
Order By: Relevance
“…Those with greater levels of ω-6 PUFAs had significantly worse outcomes, as well as increased leptin and decreased adiponectin levels [64]. However, this is controversial with others demonstrating mice fed with a ω-6-rich diet over a 24-week period to have no increased risk of synovitis when compared to those fed with ω-3 PUFAs [65]. Despite these differing results, PUFA derivatives have been trialled therapeutically.…”
Section: Implications For Oa Treatmentmentioning
confidence: 99%
“…Those with greater levels of ω-6 PUFAs had significantly worse outcomes, as well as increased leptin and decreased adiponectin levels [64]. However, this is controversial with others demonstrating mice fed with a ω-6-rich diet over a 24-week period to have no increased risk of synovitis when compared to those fed with ω-3 PUFAs [65]. Despite these differing results, PUFA derivatives have been trialled therapeutically.…”
Section: Implications For Oa Treatmentmentioning
confidence: 99%
“…The 10 µm cryosection with cryofilm was fixed on a microscope slide using chitosan and stored at 4 ºC overnight. The next day, cryosections were mechanically loaded using an atomic force microscopy (AFM, MFP-3D Bio, Asylum Research, Goleta, CA) as previously described (Votava, Schwartz, Harasymowicz, Wu, & Guilak, 2019). Briefly, the samples were tested in PBS at 37 ºC to maintain hydration and mimic physiologic conditions, respectively.…”
Section: Afm Measurement Of Neocartilage Mechanical Propertiesmentioning
confidence: 99%
“…As an alternative to in vivo testing, diet-induced obese mouse models have been used to study OA pathogenesis 17 20 primarily due to their accelerated OA onset and progression. Using a mouse model provides the opportunity to directly evaluate changes in both histological and mechanical cartilage properties in the context of diet-induced obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated increased cartilage strains in participants with high BMI 15,16 . Because it is difficult to directly evaluate cartilage mechanical properties in vivo, it is unclear whether these increased strains are due to elevated joint loading, decreased cartilage stiffness, or a combination of both.As an alternative to in vivo testing, diet-induced obese mouse models have been used to study OA pathogenesis [17][18][19][20] primarily due to their accelerated OA onset and progression. Using a mouse model provides…”
mentioning
confidence: 99%
See 1 more Smart Citation